Forest edges enhance mate‐finding in the invasive European gypsy moth, Lymantria dispar. Issue 3 (7th February 2016) - Thompson, Lily M.; Grayson, Kristine L.; Johnson, Derek M.
Abstract: Habitat type, fragmentation, and edge effects can play important roles in the mate‐finding abilities of many species. These effects can be particularly pronounced in low‐density populations, which are often found at the margins of species' ranges or at the leading edge of an invasion. The European gypsy moth, Lymantria dispar (L.) (Lepidoptera: Erebidae), is a non‐native insect defoliator in the USA and Canada, where flightless females attract male moths through pheromone production and local extirpation of low‐density populations can be due to mate‐finding failure. To assess the effects of habitat edges on the ability of gypsy moths to find mates, we conducted a release experiment with male gypsy moths using female‐baited trap arrays in fields, at forest edges, and in the forest interior. Reduced mate‐finding was expected in fields and near forest edges based on geographic variation in invasion rates, male flight behavior, and pheromone plume dynamics. However, we found that mate‐finding was highest at forest edges, reduced in fields, and lowest within the forest interior. Within an array, traps closest to the forest edge also had the highest mate‐finding, suggesting that habitat characteristics can influence male flight direction in addition to pheromone cues. These results suggest that a moderate level of forest fragmentation enhances mate‐finding ability in the gypsy moth. Understanding the relationship between habitat heterogeneity and mate‐finding success in invasive species can inform predictions of future spread and assist with management plans that target mating disruption.